Marketing Strategies and Innovation to Achieving Competitive Advantage in Muslimah Fashion - Edris, Mochamad; Lusianti, Dina; Prihandono, Agung (ADDIN, 2024)
Ethics-based marketing and religiosity are currently in the spotlight, particularly in communities where Sharia marketing strategies are crucial. This study aims to analyze the effect of Halal productservice innovation and brand religiosity marketing communication on ensuring customer satisfaction through competitive advantage. This study’s research object is Muslimah fashion products in Central Java, Indonesia, which we examine through a sample of 338 respondents who answered an online questionnaire. The study used structural equation modelling and statistical techniques to examine the positive and substantial effects of Halal productservice innovation and brand religious marketing communication on competitive advantage and customer happiness. Competitive advantage can act as a mediator in achieving customer satisfaction. Marketers must comprehend the impact of religiosity on consumer behavior, to effective marketing strategies that resonate with religious values and beliefs, particularly in markets with strong religious affiliations.